2010
DOI: 10.1017/s1138741600002225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Frequency Content on Classification of Face Gender and Expression

Abstract: 525The role of different spatial frequency bands on face gender and expression categorization was studied in three experiments. Accuracy and reaction time were measured for unfiltered, low-pass (cut-off frequency of 1 cycle/deg) and high-pass (cutoff frequency of 3 cycles/deg) filtered faces. Filtered and unfiltered faces were equated in root-mean-squared contrast. For low-pass filtered faces reaction times were higher than unfiltered and high-pass filtered faces in both categorization tasks. In the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…They concluded that low SF bandwidths (<8 cycles/face) were diagnostic for classification of happy expressions, while high SF bandwidths (>32 cycles/face) were critical for processing of sad expressions. However their dependent measures, used also in other studies (Deruelle and Fagot, 2004; Aguado et al, 2010), give no indication as to the level of SF processing. The limitations of calculating a “critical bandwidth” for processing individual facial expressions are becoming increasingly clear, as can be seen from the findings that SF information is flexibly used depending on the task type (Schyns and Oliva, 1999) and/or viewing distance (Smith and Schyns, 2009).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…They concluded that low SF bandwidths (<8 cycles/face) were diagnostic for classification of happy expressions, while high SF bandwidths (>32 cycles/face) were critical for processing of sad expressions. However their dependent measures, used also in other studies (Deruelle and Fagot, 2004; Aguado et al, 2010), give no indication as to the level of SF processing. The limitations of calculating a “critical bandwidth” for processing individual facial expressions are becoming increasingly clear, as can be seen from the findings that SF information is flexibly used depending on the task type (Schyns and Oliva, 1999) and/or viewing distance (Smith and Schyns, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…While the integration of facial identity through SF information has been well documented (Costen et al, 1996; Näsänen, 1999; Goffaux et al, 2003; Rotshtein et al, 2007; Gao and Bentin, 2011), there is less information about how our neural representation of a facial emotion is related to specific SF ranges. Studies which have focused on this issue (Vuilleumier et al, 2003; Deruelle and Fagot, 2004; Aguado et al, 2010; Kumar and Srinivasan, 2011) have examined the effect of high and low SF on the perception of emotional expressions using removal of specific SF components from the target stimuli. For example, Kumar and Srinivasan (2011) showed that low (<8 cycles/face) and high-frequencies (>32 cycles/face) are more critical for the representation of happy and sad expressions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method is also unlikely to detect minor expression variations, as only low frequency information is used. According to [3,34], expression changes mainly lie in high frequency bands. However, many of the recent face recognition algorithms are capable of handling relatively minor variations in both illumination and expression [15,17,24,28], thus these characteristics of the quality assessment method might be more of a feature than a limitation.…”
Section: Main Findingsmentioning
confidence: 99%
“…Spatial frequency discrimination is known to represent a fundamental building block of visual perception and it is essential for the analysis of fine details in a visual scene [16]. Therefore, we compared spatial frequency discrimination in normal hearing participants and in individuals with a cochlear implant.…”
Section: Introductionmentioning
confidence: 99%